KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN 4 SUNGAI NILAM JAWAI - Nurhaya, Nurhaya; Aunurahman, Aunurahman; Radiana, Usman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractTo achieve the quality of school one of them is determined by the leadership quality of the principal. The results of the last three years of SDN 4 Sungai Nilam Kecamatan Jawai Kabupaten Sambas decreased. Researchers assume that need to improve the leadership of school principals in improving the quality of schools in SDN 4 Nilam River District Jawai Sambas District. It is expected that this increase can improve the service and quality of education at SDN 4 Sungai Nilam Kecamatan Jawai Kabupaten Sambas. The focus of this research is the principal's leadership in improving the quality of school in SDN 4 Sungai Nilam Kecamatan Jawai Kabupaten Sambas, with research questions directed at: How styles, functions, factors affecting principal leadership and quality of education reality at SDN 4 Sungai Nilam Kecamatan Jawai Kabupaten Sambas? To express the question, the researcher uses qualitative research method of case study research type. To extract data and information from informants, researchers used observation techniques, interviews, and document studies. The results revealed that; style leadership of the principal in improving the quality of education in SDN 4 Sungai Nilam Kecamatan Jawai Kabupaten Sambas is a delegating style but more tendency to the style of permissive leadership. The leadership function that is applied is not in line with the concept of leadership function that experts find. Supporting factors in the form of qualifications possessed by teachers who are in accordance with the required provisions, inhibiting factors of insufficient facilities and infrastructure, the age of teachers who averaged retirement and lack of teachers. Reality quality in SDN 4 Nilam River District Jawai Sambas district, among others, the quality of raw input is low, the input quality is not complete and ineffective, and the quality of the environment is less harmonious.Keywords: Leadership, Principal, School Quality